A preliminary study on the phylogeny of the family Phengodidae (Insecta: Coleoptera) - Zaragoza-Caballero, Santiago; Zurita-García, Martín Leonel (Zootaxa, 2015)
A morphology-based phylogenetic analysis of the family Phengodidae (Coleoptera) is given. Thirty-six terminals, six genera and 60 morphological characters are included. To test the monophyly of phengodid subfamilies the terminals that belong to superfamily Elateroidea Drilocephalus Pic (Dascillidae), Pterotus LeConte (incertae sedis), Vesperelater Costa (Elateridae), Photinus Laporte (Lampyridae), Pseudotelegeusis Wittmer and Telegeusis Horn (Telegeusidae) are used as outgroups, with the remaining 30 terminals corresponding to 26 specific and four generic levels. The matrix was analyzed under a parsimony criterion under a heuristic search performed in TNT v. 2.0. One parsimonious tree was obtained. In this study two principal groups are recognized in the family Phengodidae. This study suggests for the first time a close relationship between the Telegeusidae and the subfamily Penicillophorinae.